Roasting Temperature Test On The Device Type Rotary Mechanical Coffee Roasters To Quality Arabica Coffee Types - Tommi Persada Sembiring; Achwil Putra Munir; Sumono Sumono; Ainun Rohana (Universitas Sumatera Utara, 2014)
On mechanical coffee roasters, roasting temperature needs to be considered. The temperature determines the quality of the roasting product. This study is testing the temperature at various levels of coffee roasters rotary tool on the yield and quality of coffee. The study was conducted at the Laboratory of Agricultural Engineering USU College of Agriculture in January to April 2013 using a non-factorial completely randomized design at 70 ⁰ C, 75 ⁰ C, 80 ⁰ C, 85 ⁰ C and 90 ⁰ C. Parameters measured were yield, processing capacity and water content. The results showed that the test temperature had highly significant effect on yield,had highly significant to the processing capacity, and had not significant affected the water content. The best treatment of this research is the treatment T3 (80⁰C) which produced 81.2% yield, processing capacity of 3,252 kg / hour, and the water content of 5.948% Keywords: Coffee roaster, Coffee quality, Temperature test